Pengaruh Audit Capacity Stress dan Ukuran Kantor Akuntan Publik terhadap Manipulasi Aktivitas Ril pada Perusahaan Industri Barang Konsumsi di Bursa Efek Indonesia (2013-2016) - Murhaban Murhaban; Chairunnisa Chairunnisa (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIES Banda Aceh, 2018)
This study aims to see (1) the influence of audit capacity stress and (2) size of Public Accountant offices on the manipulation of real activity on the consumer goods industry companies in Indonesia Stock Exchange. The data used in this study was secondary data of 30 samples. Sampling technique used was purposive sampling technique. The method used to analyze the relationship between the independent and dependent variable was multiple linear regression method and classical assumption test. The result of this research showed that (1) audit capacity stress influenced to manipulation of real activity in consumer goods industry companies in Indonesia Stock Exchange, (2) Size of Public Accountant offices influenced to Manipulation of Real Activity on the Consumer Goods Industry Company In Indonesia Stock Exchange. Simultaneously, audit capacity stress and size of Public Accountant offices had a positively and significant effect to manipulation of real activity in consumer goods industry company In Indonesia Stock Exchange. It was expected that the company to be able to avoid the manipulation of real activity in the company and the further researchers should add other independent variables that may influence the manipulation of the company's real activity, Such as corporate governance